Biodegradation of atrazine by three strains: identification, enzymes activities, and biodegradation mechanism. Issue 1 (31st December 2022) - Liang, Yuan; Ding, Lina; Song, Qing; Zhao, Ben; Wang, Siyu; Liu, Sheng
ABSTRACT: Biodegradation could remove atrazine from contaminated soil and water. In this work, three isolated bacterial strains D2, D6, and D17 were identified as Solibacillus, Bacillus, and Arthrobacter, respectively.They can rapidly degrade atrazine and effectively alleviate the phytotoxic effects of atrazine, with degradation efficiency following D2> D6>D17. Besides having the highest amount of exoenzyme and endoenzyme, the highest exoenzyme ratio in strain D2 also contributed to the highest atrazine degradation, as exoenzyme facilitated the direct reaction with atrazine in a short time and alleviated the stress of pollutant on strains, while more endoenzyme for D6 and D17 indicated degradation acted only after across the membrane, which needs more time to degradation. Furthermore, trzN in strain D2 can degrade atrazine to hydroxyatrazine. The biodegradation product of atrazine by strain D2 was cyanuric acid via dichlorination, hydroxylation, hydrodealkylation, methylation, dealkylation, elimination, and hydrolysis.